Barriers to HIV and sexuality education in Asia. Issue 2 (28th January 2014) - Iyer, Padmini; Clarke, David; Aggleton, Peter
Abstract : Purpose: – The purpose of this paper is to identify the key barriers to the delivery of school-based HIV and sexuality education in selected countries in Asia. Design/methodology/approach: – A review of published literature on barriers to school-based HIV and sexuality in countries in Asia was conducted, with a focus on research carried out after 1990. The paper also draws on recently undertaken national situation analyses of HIV and sexuality education conducted by the second author with support from UNESCO, as well as more general Asia-Pacific regional assessments undertaken by others. Findings: – Four key barriers to the delivery of good quality, school-based HIV and sexuality education are identified: cultural and contextual factors, policy factors, resource constraints and school-level factors. Originality/value: – The paper maps these four barriers as key areas in which action needs to occur in order to improve the delivery of school-based HIV and sexuality education. Potential levers for success are highlighted.